Experimental demonstration of quantum digital signatures over 43 dB channel loss using differential phase shift quantum key distribution - Robert J. Collins (Nature Portfolio, 2017)
Abstract Ensuring the integrity and transferability of digital messages is an important challenge in modern communications. Although purely mathematical approaches exist, they usually rely on the computational complexity of certain functions, in which case there is no guarantee of long-term security. Alternatively, quantum digital signatures offer security guaranteed by the physical laws of quantum mechanics. Prior experimental demonstrations of quantum digital signatures in optical fiber have typically been limited to operation over short distances and/or operated in a laboratory environment. Here we report the experimental transmission of quantum digital signatures over channel losses of up to 42.8 ± 1.2 dB in a link comprised of 90 km of installed fiber with additional optical attenuation introduced to simulate longer distances. The channel loss of 42.8 ± 1.2 dB corresponds to an equivalent distance of 134.2 ± 3.8 km and this represents the longest effective distance and highest channel loss that quantum digital signatures have been shown to operate over to date. Our theoretical model indicates that this represents close to the maximum possible channel attenuation for this quantum digital signature protocol, defined as the loss for which the signal rate is comparable to the dark count rate of the detectors.